Brincadeiras tradicionais na escola: construindo habilidades sociais na educação infantil - SILVEIRA JUNIOR, Paulo Wanderley Figueiredo da (2019)
This article reports the experiences of traditional games played with children between 05 and 06 years of age in a Public School Unit, located in the Val-de-Cans neighborhood in the Metropolitan Region of Belém / PA. The activities were part of the project "Playing and learning in Early Childhood Education: an experience with traditional games", proposed during the Supervised Internship in Early Childhood Education developed from March to November of 2016, as part of the Pedagogy Course of the Federal University of Pará ( UFPA). From the methodological point of view, this is a descriptive-exploratory study, of a qualitative nature, as systematized by Hatton and Smith (1995), since part of the questions born of the contact with the students and, later, dialogues with the universe (RIBEIRO and EUZÉBIO, 2013, MENEZES, 2014, ALENCAR, 2010) and the social skills (DEL PRETTE, and DEL PRETTE, 2017, CABALLO, 1996). The preliminary findings of this study, still under construction, demonstrate that traditional play in the school environment contributes to the development of social skills in children.